Prolonged Impella 5.0/5.5 support within different pathways of care for cardiogenic shock: the experience of a referral center - Pieri, Marina; Ortalda, Alessandro; Altizio, Savino; Bertoglio, Luca; Nardelli, Pasquale; Fominskiy, Evgeny; Lapenna, Elisabetta; Ajello, Silvia; Scandroglio, Anna Mara (Frontiers in Cardiovascular Medicine, 2024)
Aims Impella 5.0 and 5.5 are promising low-invasive left ventricle (LV) temporary mechanical circulatory supports (tMCS) for cardiogenic shock due to LV mechanical unloading and are paired with powerful hemodynamic support. This study aimed to analyze data and destinies of patients supported with Impella 5.0/5.5 at a national referral center for cardiogenic shock and to assess the parameters associated with myocardial recovery and successful weaning. Methods A single-center observational study was conducted on all patients treated with Impella 5.0 or 5.5 from March 2018 to July 2023. Results A total of 59 patients underwent Impella 5.0/5.5 implantation due to profound cardiogenic shock, with acute myocardial infarction being the most frequent cause of shock (42 patients, 71%). The median duration of Impella support was 13 days (maximum duration of 52 days). Axillary cannulation was feasible in almost all patients, and 36% were mobilized during support. A total of 44 patients (75%) survived to the next therapy/recovery: 21 patients experienced recovery and 15 and 8 were bridged to long-term LVAD and heart transplantation, respectively. The global survival rate was 66%. The predictors of native heart recovery at multivariate analysis were the number of days on tMCS before upgrade to Impella 5.0/5.5 [hazard ratio (HR) 0.68 (0.51–9) p = 0.0068] and improvement of LVEF within the first 7–10 days of support [HR 4.72 (1.34–16.7), p = 0.016]. Conclusions Transcatheter systems such as Impella 5.0/5.5 revolutionized the field of tMCS. Myocardial recovery is the primary clinical target. Its prognostication and promotion are key to ensure the most proficuous course for each patient from cardiogenic shock to long-term event-free survival.